Effect of nonlinear resource allocation on AIRS classifier accuracy - Hormozi, Shahram Golzari; C. Doraisamy, Shyamala; Sulaiman, Md. Nasir; Udzir, Nur Izura (Universiti Utara Malaysia, 2008)
Artificial Immune Recognition System (AIRS) is most popular immune inspired classifier. It also has shown itself to be a competitive classifier. AIRS uses linear method to allocate resources. In this paper, two different nonlinear resource allocation methods apply to AIRS. Then new algorithms are tested on 8 benchmark datasets. Based on the results of experiments, one of them increases the accuracy of AIRS in the majority of cases.